Implementasi Konsep Islah Dalam Sistem Hukum Pidana - Muhamad Jamal (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2016)
The criminal law is a law to regulate people who have committed a crime, get a reply according to his ways or used to say proportional. So the basis of the criminal pembenarnya lies in the existence of evil itself. It is based on the principle of No Criminal Without Error (geen straf zonder Schuld). And the purpose of the application of criminal law under the absolute theory is to satisfy the demands of justice by way of reply to the prisoners as well as prison spaces. Nevertheless, the penalties imposed on perpetrators of criminal acts does not reduce crime in this country. In Indonesia, we have encountered many inequities in the application of criminal law as a form of justice. It is a fact and a reality that is counter-productive of view of criminal law purposes. Therefore, it is important concept in the prevention of criminal acts without any retaliation that actually create new problems. In some countries the concept is} la> h in criminal law has been implemented as bring together victims and perpetrators so that the problems they encounter can be resolved properly and the situation returned to normal running. Islam knows the theory is} la> h} or s} ULH} u, which is "a process of dispute resolution where the parties terminate their case amicably." In the terminology of Islam in general, is} la> h} (reconciliation) can be defined as an activity that wants to bring a change of state from bad to good standing. Meanwhile, according to jurists, the word is} la> h} is defined as peace. Indonesia's criminal law does not recognize the existence of peace. Peace in criminal law is only in criminal acts that are complaint and in case of complaints do pancabutan, then it is assumed as peace or is} la> h}.